183k views
2 votes
10-12(1-x)=8(-12+6x)-14

Please I need this ASAP and I need to know how to do the steps so I get it better.Please and thanks!

User Clearly
by
5.0k points

1 Answer

6 votes

Answer:

1. Simply the left hand side by first multiplying the -12 with the (1-x) to get -12+12x since negative×negative will give you positive. So after the simplification on the left hand side you will get the expression 10-12+12x. Which will give you -2+12x on the left hand side.

2. You do same on the right hand side of the expression 8(-12+6x) -14. So you multiply the 8 with the expression in the bracket ONLY (-12+6x) then afterwards,you add the -14 it to get -96+48x-14 =-110+48x .NOTE. ADDING TO NEGATIVE NUMBERS GIVES YOU A NEGATIVE ANSWER. so -96+(-14)=-110. So after simplification. You will also get the expression-110+48x on the right hand side .

3. Then combining the two sides of the equation, the whole expression becomes

-2+12x = -110+48x. Then you group like terms by sending all number attached with a variable to the right hand side and non attached variable numbers to the left , given you

-2+110 = 48x-12x . NB .WHEN A POSITIVE NUMBER CROSSES THE EQUAL SIGN IT CHANGES TO NEGATIVE AND VICE VERSA.

4. -2+110 = 108 and 48x -12x =36x

So the final expression becomes 108= 36x

Then you divide both side by 36 ,thus 108÷36=36x÷36

Given you x= 3 as your final answer of the expression, since 108÷ 36= 3. And 36x÷36= x

User Nir Ben Yaacov
by
4.9k points